Impact study of Dompet Dhuafa beastudi scholarship program for welfare improvement Lembaga Pengembangan Insani Dompet Dhuafa - -, Eko Sriyanto; -, Pedri Hariyadi; -, Masykur Huda (2023)
Lembaga Pengembangan Insani Dompet Dhuafa (LPI DD) is a branch of Dompet Dhuafa (DD) what has the focus on developing programs in the field of education. Educational scholarships are often associated with coaching and self-development programs. This research aims to determine the impact of the capacity building program implemented by Beastudi scholarship programs. This program purpose is to invest of Indonesia human resources in the future and alleviate of poverty, where this program develops the strategic leadership and social contribution capacity. Beastudi scholarship program was born from DD’s concerns about poverty and lack of access to high education (university) in 2004. DD Beastudi scholarship program consists of Etos ID and Activist Scholarship (BAKTI NUSA). The Etos ID beneficiaries are those classified as poor, where the students as beneficiaries from poor families. The BAKT INUSA beneficiaries are categorized as activist who have the social project activity for the community. This research uses quantitative and qualitative approaches. The researcher uses random sampling and data collection techniques through questionnaires and interviews with 202 respondents of Beastudi Scholarship program. This research applies the CIBEST (Center for Islamic Business and Economic Studies) model to measure the impact of program. It can be seen based on a comparison of the social condition of beneficiaries before and after the program. Based on the results of research that have been carried out, the Beastudi scholarship program is effective and impactful program. Before receiving assistance and guidance, CIBEST analysis shows that the welfare index of Beastudi Scholarship program beneficiaries was 2.48%, then increased to 81.19% with 78,71% index changes. The program activities indicated influence on their jobs, achievement, personal development and social activities. In addition, 65,85% of respondents initiated social projects, of which 57,89% still exist. Although the mentoring, assistance and coaching programs for this program have been getting a good impact, improvements are still needed to maintain the performance and make a better impact in the future.